UKURAN PERUSAHAAN, REPUTASI KAP, dan AUDIT REPORT LAG: PERAN MODERASI PROFITABILITAS - Mohammad Fathurochman (JURNAL RISET AKUNTANSI TIRTAYASA, 2022)
This study aims to examine whether firm size, and public accountant reputation have an effect on audit report lag. Further, thus study aalso investigate wheather profitability has a moderating role on the the relationship between comapy size, public accountant reputation, and the repot lag. Current study use manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2020 as the sample of the investiation. Using 74 companies with 222 firm-year observation, this study find that the company size variable does not affect the audit report lag and profitability as the moderation variable is not able to affect the relationship of the company size to the audit report lag. Meanwhile, the public accountant reputation variable has a negative and significant effect on audit report lag and profitability as a moderation variable is able to influence the relationship between public accountant and audit report lag